DPYD genotyping and dihydropyrimidine dehydrogenase (DPD) phenotyping in clinical oncology. A clinically focused minireview. Issue 5 (8th September 2022) - Paulsen, Niels Herluf; Vojdeman, Fie; Andersen, Stig Ejdrup; Bergmann, Troels K.; Ewertz, Marianne; Plomgaard, Peter; Hansen, Morten Rix; Esbech, Peter Skov; Pfeiffer, Per; Qvortrup, Camilla; Damkier, Per
Abstract: Background: In clinical oncology, systemic 5‐fluorouracil (5‐FU) and its oral pro‐drugs are used to treat a broad group of solid tumours. Patients with dihydropyrimidine dehydrogenase (DPD) enzyme deficiency are at elevated risk of toxicity if treated with standard doses of 5‐FU. DPYD genotyping and measurements of plasma uracil concentration (DPD phenotyping) can be applied as tests for DPD deficiency. In April 2020, the European Medicines Agency recommended pre‐treatment DPD testing to reduce the risk of 5‐FU‐related toxicity. Objectives: The objective of this study is to present the current evidence for DPD testing in routine oncological practice. Methods: Two systematic literature searches were performed following the PRISMA guidelines. We identified studies examining the possible benefit of DPYD genotyping or DPD phenotyping on the toxicity risk. Findings: Nine and 12 studies met the criteria for using DPYD genotyping and DPD phenotyping, respectively. Conclusions: The evidence supporting either DPYD genotyping or DPD phenotyping as pre‐treatment tests to reduce 5‐FU toxicity is poor. Further evidence is still needed to fully understand and guide clinicians to dose by DPD activity.